Pengaruh Investasi Asing Langsung, Tenaga Kerja dan Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Indonesia - Fakhrizal Fakhrizal; Mulyadi Mulyadi; Sulthan Alfaris (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2023)
This study aims to examine how the influence of foreign direct investment, labor and government spending on economic growth partially and simultaneously on economic growth in Indonesia. This research uses descriptive quantitative with the population and sample used, namely the country of Indonesia in 2001-2020. The data analysis technique used in this study is multiple regression analysis using SPSS version 19. The results of this study indicate that foreign direct investment (X1) partially has a negative and insignificant effect on economic growth in Indonesia with a significance of 0.918. Labor (X2) partially has a positive and significant influence on economic growth in Indonesia with a significance of 0.003. Government spending (X3) partially has a positive and significant influence on economic growth with a significance of 0.008. Simultaneously foreign direct investment, labor and government spending have a positive and significant effect on economic growth in Indonesia with a significance value of 0.013.